Analysis Of Plants Included Into Lithuanian Red Book (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
55 plant species included into the Lithuanian red book were chosen and analyzed. The analysis revealed that the plants of a medium height (20 species) dominate. The flowers of 17 plant species are violet, and 48 species have green leaves. After analyzing bio ecological properties of rare plants it is possible to say heliouphilous plants dominate (37 species), majority of plants flower from the beginning of June until the end of August (50 species). 25 rare plants under research are allocated to category 2 (V) and are considered to be quickly extinct, endangered species, the population number of which and the number of individual plants decrease rapidly. The main reasons of the plant disappearance are the overgrowing of habitats by trees and bushes (58,18 %), irrigation and drainage (36,36 %) as well as intensive farming (29,09 %). The research identified that the main protective measures of rare plants are the support of the traditional farming, the limitation of hay harvesting and grazing, the maintenance of water hydro chemical , hydrological and hydrographic regime, etc.